Technology-integrated project-based learning to enhance stem competencies: A qualitative study in vocational maritime engineering education - Nafi Almuzani; Muhammad Nurdin; Ihsan Ahda Tanjung; Roy Kasiono; Saidal Siburian; Sahar Saleh (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: The maritime sector is undergoing a major transition as the IMO 2050 decarbonization agenda requires significant reductions in greenhouse gas emissions. This shift demands a new generation of marine engineers equipped with competencies in alternative fuels, emissions management, and sustainable engineering practices. However, Indonesian maritime vocational education has limited evidence-based pedagogical models for preparing students to meet these emerging industry expectations. Aim: This study examines how technology-supported project-based learning (PBL) focused on maritime decarbonization fosters the development of green marine engineering competencies and shapes the professional identity of future maritime engineers. Methods: Using an interpretive phenomenological design, the research engaged 20 marine engineering students, 5 instructors, and 6 industry practitioners over a 16-week learning cycle. Data were collected through semi-structured interviews, classroom observations, reflective journals, and project artefacts, then analyzed using Braun and Clarke’s thematic analysis. Results: Five principal themes emerged: development of systemic understanding of decarbonization technologies; collaborative construction of knowledge through distributed expertise; emergence of environmentally oriented professional identity; productive struggle as a catalyst for deep learning; and authenticity strengthened by industry involvement. Quantitative results showed notable gains in GMECI indicators, including alternative fuel knowledge (+28.8%), energy efficiency (+26.4%), environmental compliance (+24.8%), and sustainable problem-solving (+28.1%). Conclusion: Technology-integrated PBL effectively builds multidimensional green engineering competencies and provides a strong pedagogical foundation for MARPOL-aligned curriculum reform in Indonesian maritime vocational education.